c‐MYC expression and maturity phenotypes are associated with outcome benefit from addition of ixazomib to lenalidomide‐dexamethasone in myeloma - Di Bacco, Alessandra; Bahlis, Nizar J.; Munshi, Nikhil C.; Avet‐Loiseau, Hervé; Masszi, Tamás; Viterbo, Luísa; Pour, Ludek; Ganly, Peter; Cavo, Michele; Langer, Christian; Kumar, Shaji K.; Rajkumar, S. Vincent; et al. (European journal of haematology, 2020)
Objectives In the TOURMALINE‐MM1 phase 3 trial in relapsed/refractory multiple myeloma, ixazomib‐lenalidomide‐dexamethasone (IRd) showed different magnitudes of progression‐free survival (PFS) benefit vs placebo‐Rd according to number and type of prior therapies, with greater benefit seen in patients with >1 prior line of therapy or 1 prior line of therapy without stem cell transplantation (SCT). Methods RNA sequencing data were used to investigate the basis of these differences. Results The PFS benefit of IRd vs placebo‐Rd was greater in patients with tumors expressing high c‐MYC levels (median not reached vs 11.3 months; hazard ratio [HR] 0.42; 95% CI, 0.26, 0.66; P < .001) compared with in those expressing low c‐MYC levels (median 20.6 vs 16.6 months; HR 0.75; 95% CI, 0.42, 1.2). Expression of c‐MYC in tumors varied based on the number and type of prior therapy received, with the lowest levels observed in tumors of patients who had received 1 prior line of therapy including SCT. These tumors also had higher expression levels of CD19 and CD81. Conclusions PFS analyses suggest that lenalidomide and ixazomib target tumors with different levels of c‐MYC, CD19, and CD81 expression, thus providing a potential rationale for the differential benefits observed in the TOURMALINE‐MM1 study. This trial was registered at www.clinicaltrials.gov as: NCT01564537